Effects of brief exposure to campus environment on students' physiological and psychological health - Ning, Wei; Yin, Jiahui; Chen, Qiang; Sun, Xiaogang (Frontiers in Public Health, 2023)
Experiences in natural environments can enhance human wellbeing and promote the recovery of physiological and psychological health. During the COVID-19 pandemic, university students' activity off-campus was limited, thus, the campus environment was particularly important for the recovery of students' physiological and psychological health. Although the benefits of sustained natural exposure are obvious for people's physiological and psychological health, the effects of brief exposure on physiological and psychological are unclear. In the present study, four types of campus environments, including square space, dense forest space, sparse forest space, and waterfront space, were selected to explore the transient recovery effects of different types of campus environments. Sixty university students were recruited, measuring their systolic blood pressure, diastolic blood pressure, and heart rate as physical parameters to assess stress recovery. Respondents also reported scores about their personal feelings in questionnaires to evaluate their psychological states. Both physiological and psychological indicators responded to the brief natural exposure (5 min), and physiological and psychological health was restored. However, only the recovery amounts of psychological indicators were significantly different in waterfront space, dense forest space, and sparse forest space. These results indicate that being compare with other spaces, the brief exposure in the waterfront space was the most beneficial to students' psychological health recovery. This recovery was attributed to the great role played by the sense of escape, but after the brief exposure, the attraction and compatibility of the environment would hinder the psychological health recovery. In conclusion, according to tests on both physiological and psychological aspects, the waterfront environment on campus is the best choice for students' transient health recovery.